On reverberation mapping lag uncertainties. Issue 4 (11th December 2019) - Yu, Z; Kochanek, C S; Peterson, B M; Zu, Y; Brandt, W N; Cackett, E M; Fausnaugh, M M; McHardy, I M
ABSTRACT: We broadly explore the effects of systematic errors on reverberation mapping lag uncertainty estimates from javelin and the interpolated cross-correlation function (ICCF) method. We focus on simulated light curves from random realizations of the light curves of five intensively monitored AGNs. Both methods generally work well even in the presence of systematic errors, although javelin generally provides better error estimates. Poorly estimated light-curve uncertainties have less effect on the ICCF method because, unlike javelin, it does not explicitly assume Gaussian statistics. Neither method is sensitive to changes in the stochastic process driving the continuum or the transfer function relating the line light curve to the continuum. The only systematic error we considered that causes significant problems is if the line light curve is not a smoothed and shifted version of the continuum light curve but instead contains some additional sources of variability.